Anthocyanin Oligomers Induce Apoptosis and Autophagy by Inhibiting the mTOR Signaling Pathway in Human Breast Cancer Cells - Min-Gu Lee; Hyun-Jin Hong; Kyung-Soo Nam (MDPI AG, 2023)
Anthocyanin oligomers (AOs) are phytochemicals synthesized by fermenting anthocyanins extracted from grape skins and are more biologically active than monomeric anthocyanins. In this study, we evaluate the effects of an AO on triple-negative MDA-MB-231 and HER2-overexpressing SK-BR-3 breast cancer cells. The cell viability of MDA-MB-231 and SK-BR-3 cells was significantly inhibited in a concentration-dependent manner by AO treatment for 24 h, while delphinidin (a monomeric anthocyanin) had no effect on cell viability. In addition, the AO increased H2A.X phosphorylation (a marker of DNA damage), reduced RAD51 (a DNA repair protein) and survivin (a cell survival factor) protein levels, and induced apoptosis by caspase-3-dependent PARP1 cleavage in both cell lines. Surprisingly, the AO induced autophagy by increasing intracellular LC3-II puncta and LC3-II and p62 protein levels. In addition, the AO inhibited the mTOR pathway in MDA-MB-231 and SK-BR-3 cells by suppressing the HER2, EGFR1, and AKT pathways. These results demonstrate that the anti-cancer effect of the AO was due to the induction of apoptosis and autophagy via cleaved caspase-3-mediated PARP1 cleavage and mTOR pathway inhibition, respectively. Furthermore, our results suggest that anthocyanin oligomers could be considered potential candidates for breast cancer treatment.